Bordetella pertussis Adenylate Cyclase Toxin Blocks Induction of Bactericidal Nitric Oxide in Macrophages through cAMP-Dependent Activation of the SHP-1 Phosphatase - Cerny, Ondrej; Kamanova, Jana; Masin, Jiri; Bibova, Ilona; Skopova, Karolina; Sebo, Peter (Journal of immunology (Baltimore, Md., 2015)
The adenylate cyclase toxin-hemolysin (CyaA) plays a key role in the virulence of Bordetella pertussis. CyaA penetrates complement receptor 3-expressing phagocytes and catalyzes uncontrolled conversion of cytosolic ATP to the key second messenger molecule cAMP. This paralyzes the capacity of neutrophils and macrophages to kill bacteria by complement-dependent oxidative burst and opsonophagocytic mechanisms. We show that cAMP signaling through the protein kinase A (PKA) pathway activates Src homology domain 2 containing protein tyrosine phosphatase (SHP) 1 and suppresses production of bactericidal NO in macrophage cells. Selective activation of PKA by the cell-permeable analog N(6)-benzoyladenosine-3',5'-cyclic monophosphate interfered with LPS-induced inducible NO synthase (iNOS) expression in RAW264.7 macrophages, whereas inhibition of PKA by H-89 largely restored the production of iNOS in CyaA-treated murine macrophages. CyaA/cAMP signaling induced SHP phosphatase-dependent dephosphorylation of the c-Fos subunit of the transcription factor AP-1 and thereby inhibited TLR4-triggered induction of iNOS gene expression. Selective small interfering RNA knockdown of SHP-1, but not of the SHP-2 phosphatase, rescued production of TLR-inducible NO in toxin-treated cells. Finally, inhibition of SHP phosphatase activity by NSC87877 abrogated B. pertussis survival inside murine macrophages. These results reveal that an as yet unknown cAMP-activated signaling pathway controls SHP-1 phosphatase activity and may regulate numerous receptor signaling pathways in leukocytes. Hijacking of SHP-1 by CyaA action then enables B. pertussis to evade NO-mediated killing in sentinel cells of innate immunity.
Keywords: Cell Line; signální transdukce; Real-Time Polymerase Chain Reaction; AMP cyklický; myši inbrední C57BL; Signal Transduction; tyrosinfosfatasa nereceptorového typu 6; Mice; infekce bakteriemi rodu Bordetella; Cyclic AMP; kvantitativní polymerázová řetězová reakce; Macrophages; Bordetella pertussis; Enzyme Activation; zvířata; Humans; oxid dusnatý; Nitric Oxide; Bordetella Infections; aktivace enzymů; myši; makrofágy; adenylátcyklasový toxin; Adenylate Cyclase Toxin; buněčné linie; Protein Tyrosine Phosphatase, Non-Receptor Type 6; Mice, Inbred C57BL; lidé; Animals